Study of metallothionein-quantum dots interactions - Tmejova, Katerina; Hynek, David; Kopel, Pavel; Krizkova, Sona; Blazkova, Iva; Trnkova, Libuse; Adam, Vojtech; Kizek, Rene (Colloids and surfaces. B, Biointerfaces, 2014)
Nanoparticles have gained increasing interest in medical and in vivo applications. Metallothionein (MT) is well known as a maintainer of metal ions balance in intracellular space. This is due to high affinity of this protein to any reactive species including metals and reactive oxygen species. The purpose of this study was to determine the metallothionein-quantum dots interactions that were investigated by spectral and electrochemical techniques. CuS, CdS, PbS, and CdTe quantum dots (QDs) were analysed. The highest intensity was shown for CdTe, than for CdS measured by fluorescence. These results were supported by statistical analysis and considered as significant. Further, these interactions were analysed using gel electrophoresis, where MT aggregates forming after interactions with QDs were detected. Using differential pulse voltammetry Brdicka reaction, QDs and MT were studied. This method allowed us to confirm spectral results and, moreover, to observe the changes in MT structure causing new voltammetric peaks called X and Y, which enhanced with the prolonged time of interaction up to 6 h.
Keywords: fluorescence; Electrophoresis, Polyacrylamide Gel; Fluorescence; Quantum Dots; Interaction; Quantum dots; elektroforéza v polyakrylamidovém gelu; metalothionein; Electrochemical Techniques; Rabbits; Metallothionein; kvantové tečky; Animals; elektrochemické techniky; Electrochemical detection; králíci; zvířata